Research data supporting "Complex analysis of divergent perturbation theory at finite temperature" - Sun, Y; Burton, H G A (University of Oxford, 2022)
All data are generated using the Mathematica notebook "SupportingNotebook.nb" within the repository, which also provides relevant metadata. This notebook allows all data to be numerically reproduced.